2002
DOI: 10.2320/matertrans.43.1887
|View full text |Cite
|
Sign up to set email alerts
|

Influence of P Content in Electroless Plated Ni-P Alloy Film on Interfacial Structures and Strength between Sn-Zn Solder and Plated Au/Ni-P Alloy Film

Abstract: The interfacial structure and strength of solder joints between Sn-9 mass%Zn solder and plated Au/Ni-P alloy film on a Cu substrate have been investigated. Three reaction layers with 0.2 to 0.5 µm thickness were formed along the interface between the plated Ni-P alloy films and Sn-9 mass%Zn solder. The outermost layer contains a Ni-Sn intermetallic compound. The middle layer contains approximately 40 mass%Au, 35 mass%Zn, 20 mass%Ni and 5 mass%Sn. The thickness of the Au layer is 0.1 µm, so the Au layer does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…This signifies that the AuZn 3 and Al 2 (Au,Zn) compounds may inhabit the interfacial reaction between the solder and the Cu/Ni-P/Au substrate and avoid the formation of the Ni 3 Sn4 and Ni 3 P compounds. Recent studies 13,23) indicate that the weakening of the solder joint occurs at the interface between the electroless Ni-P plating layer and the solder as Ni 3 P forms during soldering. Hence, the reliability of Sn-Zn based solders on Cu/Ni-P/Au substrate is expected to be better than that of the other solders.…”
Section: Interfacial Reactions Between Sn-zn Based Soldersmentioning
confidence: 99%
“…This signifies that the AuZn 3 and Al 2 (Au,Zn) compounds may inhabit the interfacial reaction between the solder and the Cu/Ni-P/Au substrate and avoid the formation of the Ni 3 Sn4 and Ni 3 P compounds. Recent studies 13,23) indicate that the weakening of the solder joint occurs at the interface between the electroless Ni-P plating layer and the solder as Ni 3 P forms during soldering. Hence, the reliability of Sn-Zn based solders on Cu/Ni-P/Au substrate is expected to be better than that of the other solders.…”
Section: Interfacial Reactions Between Sn-zn Based Soldersmentioning
confidence: 99%
“…7) Many studies have been performed on the interfacial reaction between Sn-Zn solders and the various surface finish layers (Cu, Au/Ni/Cu and electroless Nickel-immersion Gold [ENIG]) during reflow or aging. [8][9][10][11][12][16][17][18][19] According to these previous studies, 10,20) unlike the general reaction layer formed in a Sn-base solder (solder without Zn), stable binary Cu-Zn, Au-Zn, and Ni-Zn IMCs are formed between the Sn-Zn solder and various substrates. Nevertheless, our knowledge of the mechanical properties and joint reliabilities of Sn-Zn solder joints is still insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Shohji et al also confirmed that the Sn-8Zn-3Bi showed inferior ductility to Sn-37Pb but double tensile strength of it at room temperature. 11 However, few studies have concentrated on the effect of longtime reflow, 12 despite the fact that ball grid array (BGA) solder joints may undergo several cycles of reflow during component manufacturing, soldering, and rework processes. Hence, this study aims to investigate the effect of extended reflow on the reliability of Sn-9Zn, Sn-8Zn-1Bi, and Sn-8Zn-3Bi (wt.%) solder joints on Au/Ni metallization.…”
Section: Introductionmentioning
confidence: 99%